A Mutation in Plant-Specific SWI2/SNF2-Like Chromatin-Remodeling Proteins, DRD1 and DDM1, Delays Leaf Senescence in Arabidopsis thaliana. - Eun Ju Cho; Seung Hee Choi; Ji Hong Kim; Ji Eun Kim; Min Hee Lee; Byung Yeoup Chung; Hye Ryun Woo; Jin-Hong Kim (PLoS ONE, 2016)
Leaf senescence is a finely regulated complex process; however, evidence for the involvement of epigenetic processes in the regulation of leaf senescence is still fragmentary. Therefore, we chose to examine the functions of DRD1, a SWI2/SNF2 chromatin remodeling protein, in epigenetic regulation of leaf senescence, particularly because drd1-6 mutants exhibited a delayed leaf senescence phenotype. Photosynthetic parameters such as Fv/Fm and ETRmax were decreased in WT leaves compared to leaves of drd1-6 mutants after dark treatment. The WT leaves remarkably lost more chlorophyll and protein content during dark-induced senescence (DIS) than the drd1-6 leaves did. The induction of senescence-associated genes was noticeably inhibited in the drd1-6 mutant after 5-d of DIS. We compared changes in epigenetic regulation during DIS via quantitative expression analysis of 180-bp centromeric (CEN) and transcriptionally silent information (TSI) repeats. Their expression levels significantly increased in both the WT and the drd1-6 mutant, but did much less in the latter. Moreover, the delayed leaf senescence was observed in ddm1-2 mutants as well as the drd1-6, but not in drd1-p mutants. These data suggest that SWI2/SNF2 chromatin remodeling proteins such as DRD1 and DDM1 may influence leaf senescence possibly via epigenetic regulation.